Prognostic impact of Ki-67 proliferative index in resectable pancreatic ductal adenocarcinoma. Issue 5 (10th May 2019) - Pergolini, I; Crippa, S; Pagnanelli, M; Belfiori, G; Pucci, A; Partelli, S; Rubini, C; Castelli, P; Zamboni, G; Falconi, M
Abstract: Background: Pancreatic ductal adenocarcinoma (PDAC) is an aggressive disease characterized by complex biological features and poor prognosis. A prognostic stratification of PDAC would help to improve patient management. The aim of this study was to analyse the expression of Ki-67 in relation to prognosis in a cohort of patients with PDAC who had surgical treatment. Methods: Patients who had pancreatic resection between August 2010 and October 2014 for PDAC at two Italian centres were reviewed retrospectively. Patients with metastatic or locally advanced disease, those who received neoadjuvant chemotherapy, patients with PDAC arising from intraductal papillary mucinous neoplasm and those with missing data were excluded. Clinical and pathological data were retrieved and analysed. Ki-67 expression was evaluated using immunohistochemistry and patients were stratified into three subgroups. Survival analyses were performed for disease-free (DFS) and disease-specific (DSS) survival outcomes according to Ki-67 expression and tumour grading. Results: A total of 170 patients met the selection criteria. Ki-67 expression of 10 per cent or less, 11–50 per cent and more than 50 per cent significantly correlated with DFS and DSS outcomes ( P = 0·016 and P = 0·002 respectively). Ki-67 index was an independent predictor of poor DFS (hazard ratio (HR) 0·52, 95 per cent c.i. 0·29 to 0·91; P = 0·022) and DSS (HR 0·53, 0·31 to 0·91; P = 0·022). Moreover, Ki-67 index correlated strongly with tumour grade ( P < 0·001). Patients with PDAC classified as a G3 tumour with a Ki-67 index above 50 per cent had poor survival outcomes compared with other patients ( P < 0·001 for both DFS and DSS). Conclusion: Ki-67 index could be of use in predicting the survival of patients with PDAC. Further investigation in larger cohorts is needed to validate these results. Graphical Abstract: The aim of this retrospective cohort study was to analyse the role of Ki-67 as a prognostic factor in a cohort of patients with resected pancreatic ductal adenocarcinoma. Ki-67 index was identified as an independent predictor of poor disease-specific and disease-free survival. Patients with tumour grade G3 and Ki-67 index above 50 per cent had poor survival outcomes. Ki-67 index may play a valuable role as a prognostic factor, to help characterize tumour behaviour and treatment strategies in patients with pancreatic cancer. Ki-67 and Pancreatic Cancer